Case report: Rescue treatment with add-on selexipag in a preterm infant with suprasystemic pulmonary hypertension, pulmonary capillary hemangiomatosis, and isolated pulmonary vein stenosis - Hasan, Hosan; Hysko, Klea; Jack, Thomas; Dingemann, Jens; Wetzke, Martin; Hansmann, Georg (Frontiers in Cardiovascular Medicine, 2022)
An extremely dystrophic, premature female infant, born at 25 3/7 weeks of gestational age (birth weight: 430 grams) with severe pulmonary hypertension(PH), was admitted to our neonatal ICU requiring cardiorespiratory support, including mechanical ventilation and pulmonary vasodilators such as inhaled nitric oxide(iNO) and continuous intravenous sildenafil infusions. The diagnosis of bronchopulmonary dysplasia(BPD) was made. A hemodynamically relevant, persistent ductus arteriosus(PDA) was surgically ligated after failed pharmacologic PDA closure using indomethacin and ibuprofen. The patient was discharged with an estimated 2/3 systemic pulmonary artery pressure. One month after discharge, on low-flow oxygen supplementation (0.5 L/min FiO2 100%), at the corrected age of 16 weeks, she was readmitted to our emergency department with signs of respiratory distress and circulatory decompensation. Echocardiography demonstarted suprasystemic PH. Severe PH persisted despite initiated invasive mechanical ventilation, triple vasodilating therapy (iNO, macitentan, and continuous IV sildenafil), as well as levosimendan, milrinone, and norepinephrine for recompensation from cardiac shock. Thus, we started off-label oral selexipag therapy (oral IP receptor agonist) in a smallest patient reported so far (4kg body weight). Subsequently, RV systolic pressure decreased to half-systemic, allowing to successfully weaning iNO, norepinephrine, and milrinone, and extubating the patient over four days. The infant was discharged 4 weeks after PICU admission in stable cardiorespiratory condition, with an oral, specific, triple antihypertensive PAH-targeted therapy using selexipag, macitentan, and sildenafil as well as oxygen therapy at low-flow (0.5l/min) and spironolactone. The first cardiac catheterization at the age of 9 months under the aforementioned triple PAH-targeted therapy revealed mild PH with 35 % systemic PA pressure (mPAP/mSAP=0.35) and isolated pulmonary vein stenosis. A transthoracic biopsy at the age of 12 months confirmed the diagnosis of BPD and further showed pulmonary interstitial glycogenosis and severe pulmonary capillary hemangiomatosis, without involvement of the pulmonary venules (chILD A2, A3 and B4 according to the Deutsch-Classification). The patient is currently in stable cardiorespiratory condition undergoing triple PH-targeted therapy including selexipag. This report highlights the potential benefits of the oral prostacyclin mimetic selexipag as an early add-on PH-targeted drug in chronic PH of infancy(cPHi).